Tweaking the immune system as an adjuvant for the treatment of retinal degenerations - Santos-Ferreira, Tiago; Ader, Marius (Annals of Eye Science, 2017)
Blinding diseases such as photoreceptor degenerations are debilitating conditions that severely impair daily lives of affected patients. This group of diseases are amenable to photoreceptor replacement therapies and recent transplantation studies provided proof-of-principle for functional recovery at the retinal and behavioral level, though the actual mechanism of repair still needs further investigations. The immune system responds in several ways upon photoreceptor engraftment, resulting in T-cell and macrophage infiltrations and, consequently, decrease in graft survival. Most studies on the role of the immune system suggest a detrimental effect in a therapeutic setting. Conversely, the opposite idea wherein the immune system can be activated towards a protective state was also explored in other experimental paradigms. Here, Neves and colleagues explored the potential of cross-species studies and, to a certain extent, the concept of a protective immune system in retinal degeneration and therapy. Mesencephalic astrocyte-derived neurotrophic factor (MANF) was identified in this study as a novel factor that, by modulating the immune system, can slow down photoreceptor degeneration and improve transplantation outcome.